2005
DOI: 10.1097/01.wnf.0000154222.37887.a8
|View full text |Cite
|
Sign up to set email alerts
|

Case Studies of Adjunctive Agents in Clozapine-Resistant Schizophrenic Patients

Abstract: Approximately 40%-70% of neuroleptic-resistant schizophrenic patients are nonresponders even to clozapine. Several clozapine augmentation strategies have come into clinical practice, although often without evidence-based support. This study aims to critically review all the reported case studies regarding the efficacy and safety of adjunctive agents in clozapine-resistant schizophrenic or schizoaffective patients. All published case studies examining the efficacy and safety of adjunctive agents in clozapine-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The clinical efficacy of CLZ has been improved in certain patients by coadministration of fluvoxamine (Ozdemir et al, 2001;Kontaxakis et al, 2005). Thus, Ozdemir et al (2001) reported a patient who, despite receiving a dose of CLZ that was close to the upper recommended limit, had only subtherapeutic serum concentrations of the drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical efficacy of CLZ has been improved in certain patients by coadministration of fluvoxamine (Ozdemir et al, 2001;Kontaxakis et al, 2005). Thus, Ozdemir et al (2001) reported a patient who, despite receiving a dose of CLZ that was close to the upper recommended limit, had only subtherapeutic serum concentrations of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy in some patients may be established by coadministration of the CYP1A2 inhibitor fluvoxamine, which decreases CLZ elimination and restores therapeutic concentrations of the drug in serum (Ozdemir et al, 2001;Kontaxakis et al, 2005). Fluvoxamine is unlikely to be effective in patients who eliminate CLZ rapidly via CYP3A4.…”
mentioning
confidence: 99%
“…Another predictable interaction is that between fluvoxamine, a potent inhibitor of CYP1A2 [125,126], and clozapine. A 5 to 10-fold increase in the Cp of clozapine has been observed during the coadministration of clozapine and fluvoxamine [127][128][129][130][131].…”
Section: Interactions Due To Cyp1a2 Inhibitionmentioning
confidence: 99%
“…In vivo studies in patients have established that CYP1A2 has a major role in CLZ elimination. Exposure to CYP1A2 inducers, such as cigarette smoke chemicals, has been shown to increase CLZ clearance and to compromise therapy with the drug . Inhibitory DDIs with CYP1A2 substrates and inhibitors like fluvoxamine, caffeine and fluoroquinolone antibacterials also appear to be quite predictable .…”
Section: Discussionmentioning
confidence: 99%
“…A number of clinical studies have also shown that administration of drugs that inhibit CYP1A2, such as the selective serotinin reuptake inhibitor fluvoxamine, caffeine, the fluoroquinolone antibacterials and the antipsychotic agent perazine, inhibit CLZ clearance and can precipitate CLZ toxicity [2,[23][24][25][26]. In some psychiatric patients who smoke, fluvoxamine coadministration has been found to normalize CLZ clearance and restore therapeutic concentrations in serum [27,28]. There have been similar reports of DDIs with CYP3A4 inhibitors like erythromycin, fluoxetine and imidazole antifungal agents, which also precipitate toxicity by inhibiting CLZ elimination [29][30][31][32].…”
mentioning
confidence: 99%